Development of a Customer Satisfaction Dashboard System: A Case Study of Blu-O Rhythm & Bowl, Ratchayothin Branch - ชมภูพื้น ภนิตา; คำมา ภัทราพร; แพทย์ปรีชา โชติอนันต์; นาคสุข พุทธินันท์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research, titled “Development of a Dashboard System for Visualizing Customer Satisfaction Data: A Case Study of Blu-O Rhythm & Bowl, Ratchayothin Branch”, aimed to: (1) develop a dashboard system for visualizing customer satisfaction data, and (2) evaluate users’ satisfaction with the dashboard system in supporting decision-making and service improvement. The sample group was divided into two groups: 1) 100 customers of Blu-O Rhythm & Bowl, Ratchayothin Branch, selected using convenience sampling, to provide customer satisfaction data through an online questionnaire; and 2) 12 system users, including supervisors and administrators, selected using purposive sampling, to evaluate satisfaction with the dashboard system. The research instruments consisted of: (1) a customer satisfaction questionnaire, and (2) a dashboard system for visualizing customer satisfaction data. The collected data were analyzed using descriptive statistics, including mean and standard deviation. The results indicated that the overall efficiency of the dashboard system, as evaluated by experts, was at a high level (x̄= 4.13, S.D. = 0.64), with data visualization receiving the highest rating. In addition, the overall satisfaction of system users was also at a high level (x̄= 4.20, S.D. = 0.53). The aspect with the highest satisfaction was that the system was easy to use and not complex.